BARRIERS TO ENTREPRENERUSHIP AND IN AN EAST AFRICAN CONTEXT: A CASE STUDY OF KENYA AND TANZANIA - Lalani, Afsheen (2008)
Poverty is the source of many of the developmental problems in developing countries. As a consequence of poverty, developing countries face low levels of nutrition, literacy, incomes and equality. They face high levels of mortality, diseases and illnesses, and corruption. Nevertheless, poor people care about many of the same things all human beings care about; happiness, family, livelihood, peace, security, safety, dignity and respect. However, being trapped in poverty deprives individuals to access many resources to secure basic necessities for themselves. Entrepreneurship hence can be perceived as the energy and force that can provide access to the very poor and the very rich to many resources from necessities to luxuries and a source of employment at the very least. Amid weak political and economic systems, institutions, laws and physical infrastructure that stand to bear constraints it becomes highly improbable that entrepreneurship is successful. With entrepreneurship, a private sector grows and this drives economic growth. Thus, through a qualitative study, this dissertation seeks to understand the constraints and barriers that stand in the way of successful entrepreneurship in East African developing country(s) context. Moreover, it further seeks to understand the links between entrepreneurship for economic growth and private sector development specifically, within a context of the East African developing countries of Kenya and Tanzania.